2006
DOI: 10.1017/s0022112005007494
|View full text |Cite
|
Sign up to set email alerts
|

Onset of convection in a gravitationally unstable diffusive boundary layer in porous media

Abstract: We present a linear stability analysis of density-driven miscible flow in porous media in the context of carbon dioxide sequestration in saline aquifers. Carbon dioxide dissolution into the underlying brine leads to a local density increase that results in a gravitational instability. The physical phenomenon is analogous to the thermal convective instability in a semi-infinite domain, owing to a step change in temperature at the boundary. The critical time for the onset of convection in such problems has not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

34
711
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 669 publications
(746 citation statements)
references
References 42 publications
34
711
1
Order By: Relevance
“…However, similar to thermal layers [3], the diffusion layer must thicken enough to become unstable. Analytical and numerical calculations have been performed [4][5][6][7][8][9] to predict the instability incubation time and subsequent mass transport in CO 2 -brine systems. However, the difficulties in realizing a laboratory experiment for the purposes of testing the scenario are considerable, e.g.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, similar to thermal layers [3], the diffusion layer must thicken enough to become unstable. Analytical and numerical calculations have been performed [4][5][6][7][8][9] to predict the instability incubation time and subsequent mass transport in CO 2 -brine systems. However, the difficulties in realizing a laboratory experiment for the purposes of testing the scenario are considerable, e.g.…”
mentioning
confidence: 99%
“…Non-dimensional scalings and solution techniques for the conservation of momentum, mass, and concentration are described in detail elsewhere [4][5][6][7][8][9]. Here, we discuss the di- mensionless parameters and a few details relevant to our experiment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…reason, RTI are also increasingly studied nowadays in the framework of carbon dioxide (CO 2 ) sequestration in deep saline aquifers, [8][9][10] a process for which mixing is expected to add up to the effect of chemical reactions in boosting the overall efficiency. , obtained for the absorption of CO 2 in an aqueous solution of sodium bicarbonate (NaHCO 3 , 790 mol/m 3 ) and sodium carbonate (Na 2 CO 3 , 625 mol/m 3 ) shows a quite unusual behavior.…”
mentioning
confidence: 99%
“…Conversely, one can address the question: how can chemical reactions influence natural convection or even be at the very source of hydrodynamic motion? These issues are at the heart of numerous applications in combustion, 1,2 polymer processing, 3,4 extraction techniques, 5,6 microfluidic devices, 7À9 bioconvection, 10 traveling fronts, 11À13 and CO 2 sequestration, 14,15 to name a few.To answer such questions, experimental studies have for instance investigated chemically driven convective mixing and enhanced extraction from one phase to another, induced by reactions between reactants initially contained separately in immiscible solvents. 5,16À18 In that case, it has been shown that the flow around the interface and within the bulk solutions result from (i) the coupling between transfer of chemical species at the interface, (ii) changes by the reaction of the density of the solutions which can trigger buoyancy-driven convective motions, and (iii) reaction-induced Marangoni effects, that is, fluid motion generated by surface tension changes at the immiscible interface.…”
mentioning
confidence: 99%